Oral anaphylaxis by ingestion of mite contaminated food in Panama City, 2011-2014 - Olga M Barrera (Revista Alergia México, 2015)
Background: Oral mite anaphylaxis (OMA), or pancake syndrome, occurs in atopic individuals when eating starchy foods contaminated by mites, which induce moderate or severe, even fatal, allergic reactions. This syndrome is usually seen in tropical and subtropical environments, where conditions for the growth of domestic mites are given. Oral mite anaphylaxis has been associated with hypersensitivity to acetylsalicylic acid (ASA)-non-steroidal anti-inflammatory drugs (NSAID) and physical exercise. Objective: To document the clinical and descriptive study of cases of OMA attended in City of Panama from 2011 to 2014. Material and method: A clinical descriptive and retrospective study was performed, including skin prick test to five species of domestic mites. Taxonomic identification of the mites was performed under microscope and its density per gram of food was calculated for three cases. Results: Ten cases with clinical history compatible with OMA were studied, being the pancakes the most incriminated food. The onset of symptoms occurred between 25 and 60 minutes after ingestion of the food. All patients were atopic young adults. Four of the ten patients had hypersensitivity to ASA-NSAID. The patients were positive to Prick test mites: Blomia tropicalis, Dermatophagoides pteronyssinus and Suidasia pontifica. The three samples of wheat flour studied presented high densities of mites per gram. Conclusions: The pancakes were the most incriminated food in the cases of OMA in our study. Suidasia pontifica and Blomia tropicalis seem to be the mites species of greater relevance related with this syndrome in our country.